Messaging Information System / Lit Lei Kheng - Lit , Lei Kheng (2002)
Nowdays, sending message has become a routine task in a corporate world. This message can be in the form of exchanging information or communication purposes. Previously, these tasks is completed by using pen and papers. Messaging Information System (MIS) is a software system developed using Microsoft Visual Basic 6.0 in Windows environment to make the task of sending message easier and paperless. It is especially to assist staffs in an organization of manage their daily affairs particularly those information is involved intensively. It also aims to serve as an alternative means of communication among staffs. Furthemore, it also provides facilities for staffs to know the wherebouts of another colleague. The contact details if the staff are included in the system to enable them to be easily search. Another feature of the system is the ability to store meeting records. This is to provide a reference for staffs in the future and also important to management level for decision-making. A search function will also be included in the system to assist to get the information that they desired. This system also has an on-line help features to guide the user if they are unfamiliar with the systems. In developing the MIS, the System Development Life Cycle approach had been choose. This approach has been choose because it is an organized process for established a system project plan besides developing and maintaining the system.